IWD 2021 – Aster Mekonen on running a hatchling enterprise during the COVID-19 pandemic - International Livestock Research Institute (International Livestock Research Institute, 2021)
Aster Mekonen shares her experience in running a hatchling grower enterprise in Ethiopia during the COVID-19 pandemic. Visit https://www.ilri.org/iwd2021 for more information.